Acridine Orange Fluorescence Stain for the Diagnosis of Malarial Parasite (TAJ: Journal of Teachers Association, 2009)
A total of six hundred suspected cases of malaria (150 from each centre of Rajshahi MedicalCollege Hospital and three thanas under Rajshalhi district viz. Paba, Godagari and Charghat)were examined through both thick and thin film preparation and stained by both Giemsa andacridine orange fluorescence staining respectively. All the slides in both stained preparationwere examined by three competent microbiologists in three different centres. Malarial parasitedetection in cases of Rajshahi Medical College Hospital. Paba, Godagari and Charghat. InGiemsa staining parasites were positive in 14 (9.33%), 16(10.66%),26(17.33%) and 41(27.33%)cases respectively while it was found to be positive in 21(14.00%), 36(24.00%),49(32.66%) and61(40.66%) cases in acridine orange fluorescence staining respectively. In comparison acridineorange fluorescence staining was found to be more sensitive over Giemsa staining especially inlow parasitaemic cases.doi: 10.3329/taj.v16i2.3883TAJ December 2003; Vol.16(2): 58-61